(untitled) (Research, Society and Development, 2020)
The objective of this study to evaluate the physiological quality during storage of cotton seeds collected in different positions of the gravity table after their processing. Cotton seeds were used (Gossypium hirsutum L. r.) BRS 269 - Buriti, with an initial moisture content of 9.98±0.48% wet basis (wb). Initially the seeds were processed and were later passed on the gravity and separate table. The seeds were stored in a natural environment. The treatments were collection points in gravity table: control (only benefited seeds); 0 and 16 cm (A); 16 to 32 cm (B); 32 to 48 cm (C); 48-64 cm (D); 64-80 cm (E) and 80 to 96cm (F) and storage time (0, 60, 120 and 180 days). They were evaluated during storage water content, bulk density, germination, germination speed index (GSI), low temperature germination and electrical conductivity. The moisture content and bulk density show variations during storage. During storage, germination at low temperature decreased while increasing electrical conductivity for all treatments indicating a loss of quality during storage, and these behaviors were less severe for the treatment and the greater intensity for the treatment F. Discarding the seeds of the lower part (Treatment F) gravity table during transfer contributes to improving the physiological quality of batches of cotton seeds.